The Myth of Early Globalisation: The Atlantic Economy, 1500-1800 - Pieter Emmer (Nuevo mundo - Mundos Nuevos, 2008)
In recent historiography, it has been argued that the expansion of Europe between 1500 and 1800 created a “system” in the Atlantic by which the economies of Europe, West Africa and the New World were closely interconnected by trade and migration. However, the available evidence suggests that the economic implications of such a system were of marginal importance. Rather than boosting the economy, the “Atlantic System” stimulated the expansion of European values and norms, such as private property, monogamy, the nuclear family, free labour, and the place of women and children in society.